Overview Of Mother's Knowledge About Intra Uterine Contraception Device (Iud) In The Working Area Of Penanae City Puskesmas, Bima City, 2023 - Suryati, Suryati; Nur Islamyati (Jurnal EduHealth, 2023)
The IUD contraceptive is very effective in reducing maternal mortality and controlling the population growth rate because the effectiveness rate of use is up to 99.4% and the IUD can be used for a period of 3-5 years (hormonal type) and 5-10 years (copper type). The IUD contraception device is inserted into the uterus in various shapes, consisting of plastic (polyethylene). In 2022 from 5 health centers spread throughout Bima City. Shows the number of family planning acceptors who use IUD birth control. In May 2022, there were 10.41% IUD acceptors, 9.41% at the Paruga Health Center, 21.75% at the Mpunda Health Center, 2.60% at the Rasa Na'e Timur Health Center, 5.16% at the Kumbe Community Health Center %, at the Pena Nae Health Center it was 9.84%, at the Jati Baru Health Center it was 5.64%, and at the Kolo Health Center it was -0.18%. The aim of the research is to identify the description of mothers' knowledge regarding intrauterine contraceptive devices (IUDs) in the Penanae Community Health Center working area, Bima City in 2023. This type of research is quantitative research with the design used is a Cross Sectional approach. The population in this study were all women of childbearing age who used long-term contraception in Penana Village, in 2023 there were 273 people. The sample was 51 people with a sampling technique, namely simple random sampling, namely random sampling. Based on the research results, it shows that of the 51 respondents aged 20-35 years there were 27 (53.4%), those aged >35 years were 24 (47.0%). Of the 51 respondents, the majority of mothers had an intermediate level of knowledge (high school) as many as 31 respondents (60.8%), and as many as 20 respondents had a tertiary education (39.2%). The results of this study can be concluded that the mother's age and education influence the choice of contraceptive method.